SỬ DỤNG CÔNG CỤ GIẢI TRÌNH TỰ ddRAD TRUY XUẤT NGUỒN GỐC DI TRUYỀN CỦA CÁ CHÉP CHÂU ÂU (Cyprinus carpio carpio) VÀ CÁ CHÉP AMUR (Cyprinus carpio haematopterus) LÊN QUẦN THỂ CÁ CHÉP TỰ NHIÊN CỦA VIỆT NAM - Nguyễn, Văn Quân; A. V., Nedoluzhko; Phạm, Thế Thư; Nguyễn, Đức Thế; Phạm, Văn Chiến; S. M., Rastorguev; Vũ, Quyết Thành (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
USING THE GENETIC ddRAD SEQUENCEING TECHNIQUES TO DETERMINE THE GENOME ORIGINATION AMONG DOMESTIC EUROPEAN COMMON CARP (Cyprinus carpio carpio) AND AMUR CARP (Cyprinus carpio haematopterus) TO THE WILD VIETNAMESE POPULATIONThere are four subspecies of the common carp of the world: C. carpio carpio, C. carpio haematopterus and C. carpio viridiviolaceus and C. carpio aralensis. These subspecies habit natively in Ponto-Caspian, Far-Eastern regions, Northern Vietnam and Central Asia accordingly, but they were introduced into almost all regions with suitable environmental conditions; therefore, it is one of the most widely cultured freshwater fish species in the world. In Northern Vietnam, common carp fisheries and aquacultural production have great economic importance. Investigation of the subspecies distribution among aquacultured and wild common carps is important for the understanding of the impact of human economic activity, such as aquaculture production, on the wild environment. ddRAD sequencing was used to estimate the genetic impact of aquacultured carps to wild common carp populations of Northern Vietnam. It was shown that a part of wild carp populations has significant contribution of farmed fish ancestry. For some populations, this contribution exceeds 25% of population ancestry, but the ancestry value distributed across the most specimens of population, whereas pure aquacultured specimens are quite uncommon for wild habitat.